Mobile Application with Augmented Reality as a Support Tool for Learning Human Anatomy - Iparraguirre-Villanueva, Orlando (2023)
Learning the anatomy of the human skeletal system presents several challenges in understanding the complexity of the human body. One of the most common issues is the absence of effective and accessible learning methods that enable students to gain comprehensive knowledge. Therefore, the use of technologies such as augmented reality (AR) aims to address this issue and facilitate its resolution by enabling students to engage with three-dimensional anatomical models, fostering hands-on, visualization-based learning. The aim of this study is to enhance the learning of human skeletal anatomy through the use of AR technology. The study employed a quantitative approach and a pre-experimental design, in which the experiment was conducted according to the research plan and involved 60 students. Mobile-D was used to develop the mobile application. The findings revealed that 93.3% of participants agreed that the use of augmented reality is a valuable for learning human anatomy, as it enables interactive visualization of various parts of the human body. The study also indicated that 28.3% of the students scored “Outstanding,” while 68.3% scored “Predicted.” In addition, 65% of students expressed interest in using augmented reality technology to learn anatomy.